2022
DOI: 10.3389/fpubh.2022.1025901
|View full text |Cite
|
Sign up to set email alerts
|

Reduced antibody response to COVID-19 vaccine composed of inactivated SARS-CoV-2 in diabetic individuals

Abstract: BackgroundPatients with type 2 diabetes mellitus (T2DM) are at increased risk for COVID-19 related morbidity and mortality. Antibody response to COVID-19 vaccine in T2DM patients is not very clear. The present work aims to evaluate the antibody response to the inactivated SARS-CoV-2 vaccine in this population.MethodsTwo groups of subjects with no history of SARS-CoV-2 infection were included: 63 T2DM patients and 56 non-T2DM controls. Each participant received two doses of inactivated COVID-19 vaccine. IgG ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“… 38 In the present investigation, we found that antibody response to inactivated COVID-19 vaccine was significantly reduced. Previous studies also showed that the antibody responses to various types of COVID-19 vaccines, such as mRNA vaccine, adenovirus-based vaccine, or inactivated vaccine, in diabetes patients were lower than subjects without diabetes, 15 , 25 , 28 , 29 , 39 although other studies showed that the antibody response to inactivated COVID-19 vaccines in diabetes subjects was comparable to that in non-diabetes subjects. 16 , 17 Together, the antibody response to COVID-19 vaccine in diabetes patients is relatively weaker than that in non-diabetes people.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“… 38 In the present investigation, we found that antibody response to inactivated COVID-19 vaccine was significantly reduced. Previous studies also showed that the antibody responses to various types of COVID-19 vaccines, such as mRNA vaccine, adenovirus-based vaccine, or inactivated vaccine, in diabetes patients were lower than subjects without diabetes, 15 , 25 , 28 , 29 , 39 although other studies showed that the antibody response to inactivated COVID-19 vaccines in diabetes subjects was comparable to that in non-diabetes subjects. 16 , 17 Together, the antibody response to COVID-19 vaccine in diabetes patients is relatively weaker than that in non-diabetes people.…”
Section: Discussionmentioning
confidence: 97%
“…The antibody seroconversion rates in the present study were considerably lower than the reported rates (95.7%–99.0%) in the clinical trials 32 or the reported rates (94.4%–99.5%) in real-world applications in healthcare workers in China and Turkey. 15 , 33 , 34 This might be related to the fact that study subjects enrolled in this study were hospitalized patients and were in “suboptimal” health conditions with different comorbidities, such as heart disease, and studies have shown that these patients have weaker antibody responses after COVID-19 vaccination. 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiang et al reported that the levels of anti‐RBD‐IgG and NAbs were significantly lower in patients with T2DM compared to HCs after full‐course inactivated COVID‐19 vaccines 12 . Meanwhile, Cheng et al revealed decreased titers of anti‐N/S IgG and anti‐RBD IgG in patients with T2DM compared to HCs 22 . In addition, numerous studies also indicated reduced immunogenicity to mRNA or viral vector‐based COVID‐19 vaccines after finishing full‐course immunization 4,5,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination against Covid-19 has been highly effective in combating the SARS-CoV-2 pandemic [107] , reducing acute symptoms, hospitalization, and death; however, patients with diabetes (especially those with uncontrolled glycemia) appear to be less responsive to the protective effects of the vaccination [39,108] . Moreover, vaccines are sometimes seen as potentially harmful.…”
Section: Impact Of Vaccination On Long Covid-1919 Development In Diab...mentioning
confidence: 99%